Beneficial effects of exercise, testosterone, vitamin D, calcium and protein in older men-A randomized clinical trial - Mette Midttun; Karsten Overgaard; Bo Zerahn; Maria Pedersen; Anahita Rashid; Peter Busch Østergren; Tine Kolenda Paulin; Thea Winther Pødenphanth; Linda Katharina Karlsson; Eva Rosendahl; Anne‐Mette Ragle; Anders Vinther; et al. (Wiley, 2024)
Abstract Background Due to increasing older populations worldwide, injuries, disabilities and deaths caused by falls among the elderly represent a growing human and societal problem. We aimed to improve health among men of at least 70 years of age with low‐normal to low testosterone and mobility problems by using testosterone undecanoate (TU) injections, progressive strength training, and oral supplements of vitamin D, calcium and protein. Methods This was a single‐centre, randomized, placebo‐controlled, double‐blind trial with 148 older men with a median age of 77 (73-81) years, testosterone levels at median 8 (5-9) nmol/L (full range from 1.1 to 12.9 nmol/L) and mobility problems, recruited at University Hospital of Copenhagen, Herlev Hospital, Denmark. Participants were randomized into four arms for 20 weeks: (1) TU therapy (n = 37); (2) progressive resistance training with supplements of calcium, vitamin D and protein (n = 36); (3) both interventions combined (n = 36); or (4) no intervention (n = 39). The main outcome measure was the 30‐s chair stand test, due to test performance correlating with the risk of serious fall injuries and lower extremity muscle strength. Outcome measurements were performed at baseline and after 20 weeks. Results After the intervention, the combination group receiving progressive resistance training, TU and supplements achieved a median score of 13 (11-15) compared to the control group at 10 (0-14) in the 30‐s chair stand test (P = 0.003). This median improvement of 3.0 was clinically important. Compared to the control group, participants in the combination group also increased quality of life (P < 0.05) and reduced both tiredness (P < 0.05) and leg fat (P < 0.05) and had higher variability in the RR interval (P < 0.01). The group receiving TU reduced gynoid and leg fat compared to the control group (both P < 0.05). Blood tests improved for several variables, especially in the combination group. There was no statistically significant increase in adverse effects from either the supplements or training. Conclusions In men ≥70 years old with low‐normal to low testosterone and mobility problems, supplements of testosterone, calcium, vitamin D and protein combined with progressive resistance training improved 30‐s chair stand test performance, muscle strength and quality of life. Both tiredness and leg fat were reduced, and RR interval variability was increased. Significant adverse effects were not observed.